The Relationship Between Peer Social Support and Psychological Well-Being of the Elderly in Surabaya: Hubungan Antara Dukungan Sosial Teman Sebaya dengan Kesejahteraan Psikologis pada Lansia di Surabaya - Setiawan, Eric Dwi; Mariyati, Lely Ika (Universitas Muhammadiyah Sidoarjo, 2023)
This study aims to determine the relationship between peer social support and psychological well-being in the elderly at Griya Wredha Jambangan Surabaya. This research is a type of quantitative research, using a saturated sampling method on the existing population, namely 152 elderly subjects at Griya Wreda Jambangan Surabaya. Data were collected using a psychological scale on the variables of peer social support and psychological well-being. The items on the scale were then tested for validity and reliability with the results of item validity moving from 0.659 to 0.864 out of 20 item items on the peer social support scale and item validity scores moving from 0.466 to 0.758 out of 28 item items on the psychological well-being instrument, so that can be used as a valid second instrument to use. The results of the scale reliability test obtained a score of 0.964 and 0.913 on the scale of peer social support and psychological well-being which were greater than > 0.60, which means the research scale is reliable to use. The data obtained were then processed using normality test, linearity test, classical assumption test and hypothesis testing. Through the results of the product moment correlation test, the result is 0.931** or close to 1. It can be said that there is a positive relationship between a person's social support and their psychological well-being. Referring to the significance value where 0.000 <0.05, it means that Ha is accepted, that is, there is a relationship between peer social support and the psychological well-being of the elderly, where the higher the social support received by the elderly, the higher the perceived psychological well-being. Based on the Adjusted R Square value in the tests conducted by the researchers, the results were 56.6% where the social support of friends had an effect on a person's psychological well-being, interference by other variables being studied by the researcher.